Extra Virgin Olive Oil from Stoned Olives with Oxygen Supply during Processing: Impact on Volatile and Phenolic Fraction and Sensory Characteristics - Davide Nucciarelli; Diego L. García-González; Gianluca Veneziani; Stefania Urbani; Luigi Daidone; Sonia Esposto; Agnese Taticchi; Roberto Selvaggini; Maurizio Servili (Foods, 2024)
The improvement of the extra virgin olive oil (EVOO) extraction process involves the proper management of endogenous enzymes of the olive fruit and all the technological conditions that can affect their activities. Coratina and Peranzana cultivars were processed to assess the influence of different technologies for fruit breaking (crushing and stoning) with and without controlled oxygen addition during this critical phase. The study of volatile compounds revealed that the enzymes that are responsible for their genesis during the technological process were significantly affected by oxygen addition in both the systems of fruit crushing. The results from the stoning technology proved that the quality improvement was a consequence of the prevention of the seed breaking and the oxidation catalyzed by the olive stone enzymes. In Peranzana EVOOs, it was possible to increase the aldehyde concentration up to 97% using stoning technology with a 0.2 L/min oxygen addition compared with traditional crushing. At the same time, non-significant reductions in phenolic compounds were detected when comparing crushing and stoning with and without the addition of oxygen, and similar trends were observed for the two studied cultivars. The sensory analyses confirmed the differences in phenolic and volatile composition detected in the EVOO samples.